2012
DOI: 10.26719/2012.18.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in Yemeni patients with sickle-cell disease

Abstract: Despite the general view that patients with sickle-cell disease (SCD) have iron overload, there are reports of iron deficiency in a proportion of these patients. We studied Yemeni patients aged 1-30 years with homozygous SCD to determine their iron status using a set of 4 criteria (low serum iron, low transferrin saturation, high total iron binding capacity and low mean corpuscular volume for age). Of the 75 patients, 44 had never been transfused while 31 patients had received blood transfusions but not during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
4
9
0
Order By: Relevance
“…In addition, in our study, serum iron values in transfused patients were significantly higher than those in nontransfused patients, which was statistically significant (P < 0.0000001). This is well correlated with the study by Kassim et al [13] . In our study, 59.5% of blood transfused patients and 21.2% of nontransfused patients showed increased serum iron values.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, in our study, serum iron values in transfused patients were significantly higher than those in nontransfused patients, which was statistically significant (P < 0.0000001). This is well correlated with the study by Kassim et al [13] . In our study, 59.5% of blood transfused patients and 21.2% of nontransfused patients showed increased serum iron values.…”
Section: Discussionsupporting
confidence: 93%
“…Mean value of reticulocyte count in iron-deficient group was 1.64 and in noniron-deficient group was 6.60. This correlated well with the study done by Kassim et al [13] in which mean value of reticulocyte in iron-deficient group was 2.5 and in noniron-deficient group was 9.7. This low reticulocyte count is a sign of impaired erythropoiesis, which is known to be associated with many conditions including iron, folate, and vitamin B12 deficiency, and when MCV is low for age, the reduced reticulocyte count/index supports the diagnosis of iron deficiency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patel et al [10] found that 4 In the same study, it was also found that 5 (11.62%) transfused patients and 14 (25%) non-transfused patients had decreased serum iron. Kassim et al [11] found that serum iron values were more in transfused patients as compared to non-transfused patients. The study done by Ikusemoro et al [12] showed a positive correlation between serum ferritin and number of units of blood transfused with a linear increase in serum ferritin levels seen in cumulative transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…25 Additionally, low MCV or microcytosis is one of the indicators of iron deficiency anaemia, which accounts for more than half (c 53%) of the causes of anaemia globally, with the highest burden among children between ages five and 14 years in resource-limited countries. 26,27 The incidence of iron deficiency anaemia among individuals with SCA in resource-limited settings is estimated to be around 10-11%, 28,29 particularly in the non-transfused cohort. The cross-sectional nature of this analysis did not allow a detailed analysis of the haemoglobin phenotype or determination of iron studies in our cohort.…”
Section: Discussionmentioning
confidence: 99%